APLIKASI MOBILE KUIS DAN FORUMDISKUSI MENGGUNAKAN ANDROID ( STUDI KASUS DI SMK INSAN MULIA YOGYAKARTA ) - Hendra Septian; Catur Iswahyudi; Joko Triyono (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
In order to encourage the achievement of targets compulsory quality basic education to the education level high school (SMA), it takes a learning system that can continuously guide the student in the preparation of national examinations. Therefore, this study serves to help improve the quality of education through the practice of answering the questions in the form of quizzesthat studentsto take advantage of free time more useful by playing a quiz related subjects at school. In addition this mobile application based quizzes can also build a learning community in the form of a discussion forum to help students who have difficulty completing certain matter. Applicationson Android and the web client server model. Mobile application is used for students and teachers. Web applications used by employees of the administration and the teachers to create questions. Object study site is subject to higher secondary schools ranging from subject Mathematics, Bahasa Indonesia, English, Natural Science, Social Studies and Civics. Applications can be installed and run on mobile devices that use the Android operating system and is run by internet networks with separate data storage method that is planted on a server through a particular domain and hosting.